IoT based real-time synchronized clock - Haq, Mohammad Moinul; Rabbi, Aakash; Jamil, Mustafa; Zahin, Araf (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.